2018
DOI: 10.3390/en11102861
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Hybridization of Heuristic Techniques for Residential Load Scheduling

Abstract: With the emergence of the smart grid, both consumers and electricity providing companies can benefit from real-time interaction and pricing methods. In this work, a smart power system is considered, where consumers share a common energy source. Each consumer is equipped with a home energy management controller (HEMC) as scheduler and a smart meter. The HEMC keeps updating the utility with the load profile of the home. The smart meter is connected to a power grid having an advanced metering infrastructure which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Therefore, for solving the same problem, it is impossible to conclude which algorithm is absolutely dominant. A performance comparison of several optimization algorithms while solving residential load scheduling problem is presented in [76]. This research also confirmed that GA in comparison to all other algorithms have advantages and disadvantages, but that it always give satisfying results along with using a reasonable amount of computational resources.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, for solving the same problem, it is impossible to conclude which algorithm is absolutely dominant. A performance comparison of several optimization algorithms while solving residential load scheduling problem is presented in [76]. This research also confirmed that GA in comparison to all other algorithms have advantages and disadvantages, but that it always give satisfying results along with using a reasonable amount of computational resources.…”
Section: Introductionsupporting
confidence: 54%
“…Also centralised but considering renewable energy technologies to improve energy efficiency and reduce costs through optimisation algorithms, approaches in the work by the authors of [20] focus on the context of microgrids and storage at residential and commercial building environments. In addition, heuristics based on genetics algorithms [21] and neural networks [22] work on the scheduling of the consumer consumption to save the peak formation. Their simulation results show that the proposed algorithms reduce the peak-to-average ratio and help users minimise their energy expenses without compromising comfort.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, to protect the environment and climate change from heavy CO 2 emissions due to massive utilization of conventional energy resources, it is required to either optimize the energy consumption trends or to integrate VER or the combination of both [4]. Because, studies show that it is more beneficial to develop hybrid energy management solutions [5]. In doing so, the load management problem can also be solved at the micro-grid level by investigating the energy consumption of individual residential consumers rather than aggregated demand.…”
Section: Introductionmentioning
confidence: 99%